Advances in gadolinium-based composite materials for neutron and gamma-ray shielding - Chen, Jian; Zhang, Xingwu; Xiao, Weixiang; Pan, Duoqiang; Wu, Weiwei (Frontiers in Materials, 2025)
With the significant advancements in nuclear technology, countries have invested considerable research into radiation shielding and protection materials. Neutrons and gamma photons have strong penetrating abilities, which can directly jeopardize human health or lead to the failure of electronic components. Therefore, developing high-performance materials for neutron and gamma photon radiation shielding has become a critical priority. Gadolinium (Gd), a rare earth element with the largest neutron absorption cross-section among natural elements, performs excellently as a neutron absorber. Gd-containing radiation composite shielding materials are typically classified into four main categories based on their matrix: metal-based, glass-based, ceramic-based, and polymer-based. This paper reviews the current research status of these four types of radiation shielding materials. It provides a comprehensive summary and evaluation of each material’s preparation processes, microstructures, mechanical properties, and shielding performance. Additionally, the paper discusses the role of Gd in each type of matrix material and addresses the current challenges in the field.